Supplementation of Rosemary Leaves (Rosmarinus officinalis) Powder Attenuates Oxidative Stress, Inflammation and Fibrosis in Carbon Tetrachloride (CCl4) Treated Rats - Abu Taher Sagor, Md; Mahmud Reza, Hasan; Tabassum, Nabila; Sikder, Biswajit; Ulla, Anayt; Subhan, Nusrat; Hemayet Hossain, Md; Ashraful Alam, Md (Current Nutrition & Food Science, 2016)
Objective: Rosmarinus officinalis (Family: Lamiaceae) has been used as a food preservative and flavoring agent. This plant also contains antioxidant activity and can be used as a possible therapeutic alternative for various diseases. The purpose of this study was to explore the antifibrotic effect of Rosmarinus officinalis in carbon tetrachloride (CCl4)-induced liver dysfunction in rats. Methods: Female Long Evans rats (10-12 weeks old) were divided equally into four different groups such as control, control+rosemary, CCl4 and CCl4+rosemary (6 rats in each group). Over the course of the development of liver dysfunction, several oxidative stress parameters, increased liver marker enzymatic functions were determined in CCl4 treated rats. Moreover, histological assessments were also done in liver section for inflammatory cells infiltration and fibrosis using hematoxylene and eaosin staining and Sirius read staining. Results: CCl4 administration significantly increased the Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), and Alkaline Phosphatase (ALP) activities in plasma which was decreased by Rosmarinus officinalis leaves powder supplementation. Rosmarinus officinalis prevented the rise of lipid peroxidation, nitric oxide and Advanced Oxidative Protein Product (AOPP) in plasma and liver tissues in CCl4 treated rats. Histological studies also showed massive necrosis, periportal inflammation, iron deposition and fibrosis in liver of CCl4 treated rats which were further ameliorated by Rosmarinus officinalis powder supplementation. Conclusion: In conclusion, this study revealed the antifibrotic activity of Rosmarinus officinalis powder on experimental hepatic damage and also suggests a potential therapeutic use of Rosmarinus officinalis as an alternative therapy for hepatic disorders.
Keywords: Carbon tetrachloride